A novel DEAH-box helicase 37 mutation associated with differences of sex development - Wan, Yun; Yu, Richeng; Luo, Jianhua; Huang, Ping; Zheng, Xingju; Sun, Liqun; Hu, Kui (Frontiers in Endocrinology, 2023)
Objective: To determine the genetic etiology of a family pedigree with two patients affected by the differences of sex development (DSD). Methods: Clinical characteristics of the patients. Exome sequencing result and in vitro functional studies. Results: The 15-year-old proband reared as female presented with delayed puberty and short stature associated with atypical genitalia. Hormonal profile showed hypergonadotrophic hypogonadism. Imaging studies revealed absence of uterus and ovaries. The karyotype confirmed a 46, XY pattern. Her younger brother showed micro-penis, hypoplastic scrotum with nonpalpable testis and hypospadias. Laparoscopic exploration was performed on the younger brother. Streak gonads were found and removed due to the risk of neoplastic transformation. Post-operative histopathology showed co-existence of Wolffian and Müllerian derivatives. Whole exome sequencing identified a novel mutation (c.1223C>T, p. Ser408Leu) in Asp-Glu-Ala-His-box helicase 37 gene, which was found to be deleterious by in silico analysis. Segregation analysis of the variant displayed a sex-limited, autosomal-dominant, maternal inheritance pattern. In vitro experiments revealed that the substitution of 408Ser by Leu caused decreased DHX37 expression both at mRNA and protein levels. Moreover, β-catenin protein was upregulated, and p-53 protein was unaltered by mutant DHX37. Conclusions: We described a novel mutation (c.1223C>T, p. Ser408Leu) of DHX37 gene associated with a Chinese pedigree consisting of two 46, XY DSD patients. We speculated that the underlying molecular mechanism might involve upregulation of β-catenin protein.